2020
DOI: 10.1109/access.2020.2984851
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Step Short-Term Wind Power Prediction Based on Three-level Decomposition and Improved Grey Wolf Optimization

Abstract: Wind power prediction is of great importance in enhancing wind energy penetration. This paper proposes a novel wind power prediction method which combining three-level decomposition with optimized prediction method. In the decomposition part, the Wavelet Packet Decomposition (WPD) is introduced as the first level decomposition, then the obtained sub-series are further decomposed by Variable Mode Decomposition (VMD). At last, Singular Spectrum Analysis (SSA) is carried out for each Intrinsic Mode Function (IMF)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 45 publications
0
8
0
Order By: Relevance
“…When |B| > 1, the wolves move independently to search for their prey. When |B| < 1, wolves would act collectively to capture the searched prey [19]. At the same time, the whole process would make the selected wolf always have the best quality searchability.…”
Section: Improved Grey Wolf Optimization Supportmentioning
confidence: 99%
“…When |B| > 1, the wolves move independently to search for their prey. When |B| < 1, wolves would act collectively to capture the searched prey [19]. At the same time, the whole process would make the selected wolf always have the best quality searchability.…”
Section: Improved Grey Wolf Optimization Supportmentioning
confidence: 99%
“… CEEMDAN-Multi-objective GWO-KNEA 231 Parameters of KNEA. KELM-Improved GWO (IGWO) 232 Parameters of KELM. Improved multi-objective GWO 233 Parameter of ANN models (SVM, GRNN, BPNN, ANFIS, LSTM, and NARNN).…”
Section: State-of-the-art Deterministic Forecasting Methodsmentioning
confidence: 99%
“…Liu et al used the WPD-EMD-ELM model for wind speed prediction and the results showed that the model outperformed other hybrid models (Liu et al 2018a ). Han and Tong decomposed the data first using WPD-VMD-SSA and then predicted short-term wind power by KELM, while adding an Improved Grey Wolf Optimization (IGWO) to the model, and the results showed that the final model outperformed other comparative models (Han and Tong 2020 ) and so on.…”
Section: Introductionmentioning
confidence: 99%